ANALISIS PERBANDINGAN BRAND PERSONALITY SMARTPHONE SAMSUNG DAN APPLE - Firda Naufal Azizah (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Smartphones are one of the fastest growing technology media. In recent years, Smartphones have made considerable progress in all aspects, especially hardware. With the incessant development of technology, consumers must start setting personal standards. Brand personality plays an important role in brand positioning and plays an important role in brand attributes, because consumers are looking for products that reflect their own image. This research will explain how Apple and Samsung brand personality compare to Indonesian society, through five dimensions of brand personality namely sincerity, excitement, competence, sophistication, ruggedness. Data collection was conducted through questionnaires to 400 respondents who knew or used Samsung and or Apple smartphones in Indonesia. This study used descriptive analysis to answer how Samsung and Apple brand personality as well as comparative analysis to explain each brand personality of Samsung and Apple, and the analysis technique used was a different test of Mann Whitney. The results showed that there was a difference in the average value of brand personality in both brands. Apple outperformed Samsung on the entire average brand personality dimension. A significant difference in the Samsung and Apple brands lies in the competence dimension. It can be interpreted that Apple has a brand personality that matches the characteristics of its users.